Congenital chylothorax: a case report - Ambrosio,Bruna (2018)
Congenital chylotorax is the most common form of pleural effusion in the prenatal period, although it is rare. The etiology of this condition isn't clear, but it is thought to be related to congenital malformations of the lymphatic system. The overall mortality rate is 25%-50%, but it could be higher. Congenital chylotorax complicated with hydrops in a premature newborn is an uncommon and serious clinical problem. We report a case of a congenital bilateral chylothorax with early and severe prenatal presentation. The outcome was bad, with neonatal death, despite all the efforts in his management.